2016
DOI: 10.1002/jpln.201600043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus management in rice–mungbean rotations on sandy soils of Cambodia

Abstract: Nitrogen (N) and phosphorus (P) deficiencies are key constraints in rainfed lowland rice (Oryza sativa L.) production systems of Cambodia. Only small amounts of mineral N and P or of organic amendment are annually applied to a single crop of rainfed lowland rice by smallholder farmers. The integration of leguminous crops in the pre‐rice cropping niche can contribute to diversify the production, supply of C and N, and contribute to soil fertility improvement for the subsequent crop of rice. However, the perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Despite its many benefits, the use of cover cropping by farmers is often less utilized than is desirable. Barriers to adoption include the following: benefits are siteand soil-specific, establishment and management problems exist, and climatic variability can lead to uncertainty in outcome (Ro et al 2016). Water use by the cover crop may be a problem under drought stress, resulting in lower yields and P uptake (Turmel et al 2011).…”
Section: The Termination Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its many benefits, the use of cover cropping by farmers is often less utilized than is desirable. Barriers to adoption include the following: benefits are siteand soil-specific, establishment and management problems exist, and climatic variability can lead to uncertainty in outcome (Ro et al 2016). Water use by the cover crop may be a problem under drought stress, resulting in lower yields and P uptake (Turmel et al 2011).…”
Section: The Termination Methodsmentioning
confidence: 99%
“…Datasets from a single field experiment that had been published in several articles (e.g., yield and soil microbiology in different papers) were merged into a single dataset when possible. Details of the studies used (Weerakoon et al 1992;Medhi and Datta 1996;Boswell et al 1998;Vanlauwe et al 2000;Kabir and Koide 2002;Somado et al 2003;Jensen et al 2005;Rutunga et al 2008;Wang et al 2008;Eichler-Löbermann et al 2008;Oikeh et al 2008;Takeda et al 2009b Ro et al 2016;Pavinato et al 2017) and the extracted data can be found in supplementary material (S1+S2). The data were extracted from the publications using the shareware-tool DataThief III (Tummers 2006) and the open source software Tabula (Aristarán et al 2017).…”
Section: The Meta-analysismentioning
confidence: 99%
“…Thus, provided the environmental conditions permit it, growing pre‐rice green manures can be efficient in avoiding the build‐up of soil NO 3 ‐N and improve systems N balances, as has been shown in the present study, and earlier for example from rice‐wheat rotations in Nepal ( Becker et al., 2007). While grasses have been reported to be more effective in trapping and recovering soil N than legumes ( Baldwin and Creamer , 2006), substantial amounts of 35 ( Ro et al., 2016), 40 ( Asante et al., 2017), 60 ( Ladha et al., 2000) and up to 120 kg N ha −1 ( Becker et al., 1995) can be provided additionally every year by biological N 2 fixation when integrating adapted legumes into a rainfed rice rotation. Amounts of native soil N saved by transition season legumes or by a temporary N immobilization following the application of straw have been estimated to range from 10 ( George et al., 1998), over 25–30 ( Yu et al., 2014; Asante et al., 2017), and up to > 60 kg N ha −1 ( Becker et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Such strategies add substantial amounts of biologically‐fixed N when legumes are grown and incorporated as green manure ( Sullivan et al., 2012). Different concepts of native soil N conservation and N addition by biological N 2 fixation, sole, or in combination, have been shown to enhance grain yields in the short‐term ( Becker et al., 1995) and to maintain soil fertility in the longer‐term in rice‐based production systems of the Philippines ( George et al., 1998), Cambodia ( Ro et al., 2016), and Nepal ( Becker et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Mungbean as green manure [96] China Relative contributions of N to wheat grain from mungbean: 48.4% -68.1%.…”
Section: Residual Effects In Crop Rotationsmentioning
confidence: 99%